금강수계의 물환경기준과 목표수질 설정방안, Establishment of Water Quality Standards and Water Quality Target in the Geum-River Basin - 이상진(Sang-Jin Yi) (Journal of Korean Society on Water Environment, 충남발전연구원, 2013)
According to Geum-River restoration project, given conditions for management of water environment in the Geum-River were changed. Because of those changes, this study was investigated the establishment of water quality standards and water quality target in the Geum-River basin. For management of water environment in the Geum-River, the sub-basins and watersheds are newly divided and the water quality and ecosystem standards in the sub-basins are reestablished. Considering the consistency of water environment policy and legal system, the legal name of sub-basins and watersheds are unified. TMDL (total maximum daily load) should be implemented in the sub-basin where exceeds the water quality standards and the number of water pollutant among the water quality parameters which exceeds the water quality standards are extremely minimized. The water quality target of water pollutant for implementation of TMDL should be established same or higher concentration of water quality standards. 1. 서 론 1) 우리나라 4대강 중의 하나인 금강은 상류에 생･공용수 확보와 홍수조절, 전력생산 등을 위하여 대청댐과 용담댐이 건설되었고, 서해로 유출하는 지점에는 농업용수 이용과 바닷물에 의한 염해 방지를 위하여 금강하굿둑이 설치되어 운영되어 왔다. 또한, 최근에는 금강정비사업이 추진되었는 데(MLTMA, 2009) 대청댐과 금강하굿둑 사이에 3개 보(세 종보, 공주보, 백제보)를 설치하였고, 보가 설치된 구간에는 홍수조절과 유수량 확보를 위하여 금강유로를 대폭 정비한 결과 수심이 깊어지고 유수단면적이 확장되어 유속이 느려 졌으며, 보 주변과 강변에는 수변공원을 조성하는 등으로 물환경 여건이 크게 달라졌다. 한편, 금강중류 유역에는 충청남도 연기군 전체와 공주시및 충청북도 청원군 일부지역을 포함한 세종특별자치시가 2012년 7월 1일부터 출범하였고, 2012년 말부터 정부세종 청사 개청 및 정주인구를 위한 아파트건립과 각종 개발사업 등이 진행 중에 있어 유기물 등 수질오염물질 유입량이 점진적으로 증가할 전망이다. 이와 같이 금강의 물환경관리 여건이 크게 변화함에 따라 금강 물환경관리를 위한 유역의 구분과 수질 및 수생태계에 관한 환경기준을 검토하고, 2004년부터 시행하고 있는 수질오염총량관리제의 목표수질과 관계성에 대하여 고찰하였다.
Keywords: 금강수계; 물환경기준; 목표수질; 설정방안; Water Quality Standards; Water Quality Target; Geum-River Basin; TMDL